High‐Yielding Diastereoselective syn‐Dihydroxylation of Protected HBO: An Access to D‐(+)‐Ribono‐1, 4‐lactone and 5‐O‐Protected Analogues. Issue 7 (8th January 2019) - Moreaux, Maxime; Bonneau, Guillaume; Peru, Aurélien; Brunissen, Fanny; Janvier, Marine; Haudrechy, Arnaud; Allais, Florent
Abstract : A diastereoselective chemoenzymatic synthetic pathway to D‐(+)‐ribono‐1, 4‐lactone, a versatile chiral sugar derivative widely used for the synthesis of various natural products, has been designed from cellulose‐based levoglucosenone (LGO ). This route involves a sustainable Baeyer‐Villiger oxidation ofLGO to produce enantiopure (S)‐γ‐hydroxymethyl‐α, β‐butenolide (HBO ) that is further functionalized with various protecting groups to provide 5‐ O ‐protected γ‐hydroxymethyl‐α, β‐butenolides. The latter then undergo a diastereoselective and high‐yielding syn ‐dihydroxylation of the α, β‐unsaturated lactone moiety followed by a deprotection step to give D‐(+)‐ribono‐1, 4‐lactone. Through this 4‐step synthetic route fromLGO, D‐(+)‐ribono‐1, 4‐lactone is obtained with d.r. varying from 82:18 to 97:3 and in overall yields between 32 and 41 % depending on the protecting group used. Moreover, valuable synthetic intermediates 5‐ O ‐ tert ‐butyldimethylsilyl‐, 5‐ O ‐ tert ‐butyldiphenylsilyl‐ as well as 5‐ O ‐benzyl‐ribono‐1, 4‐lactones are obtained in 3 steps fromLGO in 58, 61 and 40 %, respectively. Abstract : A diastereoselective synthetic pathway leads to valuable D‐(+)‐ribono‐1, 4‐lactone and its 5‐ O‐ protected derivatives starting from cellulose‐derived levoglucosenone.